Intensity-Dependent Changes in Quantified Resting Cerebral Perfusion With Multiple Sessions of Transcranial DC Stimulation - Sherwood, Matthew S.; McIntire, Lindsey; Madaris, Aaron T.; Kim, Kamin; Ranganath, Charan; McKinley, R. Andy (Frontiers in Human Neuroscience, 2021)
Transcranial direct current stimulation (tDCS) to the left prefrontal cortex has been shown to produce broad behavioral effects including enhanced learning and vigilance. Still, the neural mechanisms underlying such effects are not fully understood. Furthermore, the neural underpinnings of repeated stimulation remain understudied. In this work, we evaluated the effects of the repetition and intensity of tDCS on cerebral perfusion [cerebral blood flow (CBF)]. A cohort of 47 subjects was randomly assigned to one of the three groups. tDCS of 1- or 2-mA was applied to the left prefrontal cortex on three consecutive days, and resting CBF was quantified before and after stimulation using the arterial spin labeling MRI and then compared with a group that received sham stimulation. A widespread decreased CBF was found in a group receiving sham stimulation across the three post-stimulation measures when compared with baseline. In contrast, only slight decreases were observed in the group receiving 2-mA stimulation in the second and third post-stimulation measurements, but more prominent increased CBF was observed across several brain regions including the locus coeruleus (LC). The LC is an integral region in the production of norepinephrine and the noradrenergic system, and an increased norepinephrine/noradrenergic activity could explain the various behavioral findings from the anodal prefrontal tDCS. A decreased CBF was observed in the 1-mA group across the first two post-stimulation measurements, similar to the sham group. This decreased CBF was apparent in only a few small clusters in the third post-stimulation scan but was accompanied by an increased CBF, indicating that the neural effects of stimulation may persist for at least 24 h and that the repeated stimulation may produce cumulative effects.